JUSTIFICATION OF THE EFFICIENCY INDICATOR OF FORCING A WATER OBSTACLE BY ARMORED TRANSPORTERS DURING COMBAT ACTIONS - KOVTUN, ANATOLII; KUPIN, SERHII; YARMOLIUK, VADYM; SUKHORUKOV, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The work substantiates the relevance of solving the problem of determining the efficiency indicator of the use of armored wheeled vehicles when carrying out measures to overcome water obstacles during hostilities, taking into account the fact that combat vehicles may receive various types of damage from the enemy's weapons when performing their assigned tasks.  To determine the effectiveness of the forcing task of water obstacles by armored personnel carriers during the conduct of hostilities, it is proposed to use a new coefficient of effectiveness of the execution of the combat task, which consists of the coefficients of effectiveness, efficiency and resource provision of the execution of the task. The paper proposes a mathematical model for determining the efficiency indicator of forcing through a water obstacle by armored personnel carriers during combat operations actions if they have combat damage. An armored personnel carrier has stability on water if the metacenter lies above its center of mass. If the total flow of water entering due to damage to the body of the armored personnel carrier is less than or equal to the total productivity of the means of water pumping, then the time of movement of the armored personnel carrier and the distance that it passes in a damaged state, not limited, and the car will reach the shore. If the total flow of water is greater than the productivity of the means of water pumping, then there will be a gradual accumulation of water in the body of the armored personnel carrier. As the water accumulates, the static pressure and the total flow of water due to damage will increase, and the speed of the armored personnel carrier will decrease, the time for forcing the water obstacle will increase. The given dependencies for evaluating the effectiveness of the tasks of forcing the water obstacle by armored personnel carriers during hostilities in the presence of combat damage, allow to determine the influence on the efficiency index of various components and outline the ways to meet the specified requirements for modern models of floating vehicles. The work gives examples of calculations using a mathematical model for determining the efficiency indicator of forcing through a water obstacle by armored personnel carriers during combat operations in the presence of combat damage.
Keywords: efficiency; indicator; armored personnel carrier; forcing